1996
DOI: 10.1002/(sici)1097-4547(19960901)45:5<513::aid-jnr1>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Time course and regional expression of C-FOS and HSP70 in hippocampus and piriform cortex following soman-induced seizures

Abstract: The time course of induction of the proto‐oncogene c‐fos and the inducible heat shock hsp70 gene was studied from 5 minutes to 24 hours at both transcriptional (c‐fos and hsp70 mRNA) and translational levels (C‐FOS and HSP72 proteins) in the rat hippocampus and piriform cortex (Pir) after soman‐induced seizures. Induction of c‐fos was noticed as early as 5 minutes after seizures onset in all fields of hippocampal formation (CA1, CA3, CA4, and dentate gyrus) and in piriform cortex. The most intense induction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Other studies (Ikeda et al, 1990; Chaudhuri, 1997; Chaudhuri et al, 2000) indicate that c-Fos mRNA expression in fact may be above baseline levels already after 15 min of stimulation. Stimuli such as dehydration (da Silveira et al, 2007) tactile exploration (Melzer and Steiner, 1997; Bisler et al, 2002) visual stimulation (Baille-Le Crom et al, 1996), mechanical trauma (Buytaert et al, 2001), encephalic lesion (Schreiber et al, 1993), stress (Cullinan et al, 1995) showed different c-Fos expression patterns than those with PTZ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Ikeda et al, 1990; Chaudhuri, 1997; Chaudhuri et al, 2000) indicate that c-Fos mRNA expression in fact may be above baseline levels already after 15 min of stimulation. Stimuli such as dehydration (da Silveira et al, 2007) tactile exploration (Melzer and Steiner, 1997; Bisler et al, 2002) visual stimulation (Baille-Le Crom et al, 1996), mechanical trauma (Buytaert et al, 2001), encephalic lesion (Schreiber et al, 1993), stress (Cullinan et al, 1995) showed different c-Fos expression patterns than those with PTZ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using mice and rats show Fos and Jun gene expression in several regions of the central nervous system when animals are exposed to a wide range of stimuli like trauma ( 7 ), water stress ( 8 ), fear ( 9 ), odors, intraparenchymal injections of various compounds ( 10 , 11 ), and visual stimuli ( 12 ). Basal expression of c-Fos has been studied in several species, including mice, rats, cats, monkeys, and humans.…”
Section: Introductionmentioning
confidence: 99%